Effects of drainage condition on the stress-strain behavior and pore pressure buildup of sand-PET mixtures. (10th February 2020) - Shariatmadari, Nader; Karimpour-Fard, Mehran; Hasanzadehshooiili, Hadi; Hoseinzadeh, Saman; Karimzadeh, Zaniar
Highlights: CD and CU triaxial behavior of sand-PET mixtures are evaluated. Contractive-dilative behavior of sand-PET mixtures are investigated. Models are proposed for the stress and pore pressure based on the triaxial tests. Three-dimensional, graphical, parametric studies are presented. Sensitivity analysis is conducted on the shear stress in both CD and CU cases. Abstract: Recycling and usage of Polyethylene Terephthalate (PET) in civil constructions will not only decrease the environmental challenges, but also it will result in considerable saving in the overall project costs. Introducing PET chips as a capable material for the improvement of sands, this paper presents the results of consolidated drained (CD) and undrained (CU) triaxial tests on different sand-PET mixtures. Applying four different PET contents and two relative densities, tests are conducted under a wide range of confining pressures from 50 kPa to 500 kPa and the mobilized shear stress and the pore water pressure buildup are studied. Changing in the drained and undrained dilative-contractive behavior of sand-PET mixtures in different PET contents, relative densities and confining pressures showed the multi-variable nature of the problem emphasizing on the need for the comprehensive stress-strain modeling of mixtures. Such a behavior is then assessed through proposing new predictive, evolutionary models for the shear stress and the pore pressure based on the PET content, relative density, confining pressure and axial strain. Parametric studies showed that (0.2–0.3)% PET content, also, (2–4)% axial strain are determinative ranges for the evaluation of undrained and drained shear stresses of mixtures, respectively. A three-dimensional, graphical comparison using the developed relationships introduced the (0.5–0.7)% range as the critical value for the PET content distinguishing the drained and undrained behavior of mixtures. Next, according to the sensitivity analysis, confining pressure and axial strain are, respectively, presented as the most influencing parameters on the drained and undrained, mobilized shear stresses.